Research collaboration stories : Communication as Constitutive of temporary organization - A. Saludadez, Jean (2004)
Seeking a form of knowledge that places communication as constitutive of temporary organization, I explored the temporary organization that is research collaboration as it is structured and restructured in stories people tell. I fiamed the research problem in terms of a muted voice of a group of people in the research collaboration discourse: What research collaboration stories do researchers tell? And how is the temporary organization that is research collaboration structured and restructured in the stories they tell? I conversed with 30 forestry researchers in three Southeast Asian universities with which I had access by virtue of my affiliation as student, as staff and as a scholar of a consortium of universities. From the recurring symbols and repeated expressions in their narratives, and the sequencing of repeating or not repeating a collaborative act, I derived two types of stories, "the partner story" and "the not partner story". The partner story tells of a continuing partner relationship, the not partner story of a not . . . 111 continuing partner relationship. I retold the partner and the not partner stories through eight stories in various settings. Drawing fi-om Taylor et al's definition of organization as "a construction of text made out of conversation", I made an interpretation that the temporary organization that is research collaboration is seen in the configuration and reconfiguration of the partner relationship in the partner and the not partner stories: first, at the level of text, as narrative structure and as networked transcendent; and then, at the level of conversation, in the identity and in the indeterminacy of partner relationship. The collaborative structures took shape and continued to take shape in ongoing research collaboration conversations. By departing fiom the usual conception of network as information link, the study surfaced existing networks of partner relationship obscured in managerialist stories and in the literatures on research collaboration. The networks are "hidden transcripts" existing but unseen as the researchers' experiences and perspectives are unheard in the centered discourse. I structured the dissertation also as story to illustrate the constitutive property of communication and to suggest that science as organized knowledge is also communicatively constituted.